2003
DOI: 10.1073/pnas.0930140100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes occurring in established tumors rapidly stimulate new antibody responses

Abstract: Cre-loxP ͉ immunosurveillance ͉ EGFP ͉ SEREX ͉ cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The identification of EGFP 200 -208 as an H-2Kd-restricted cytotoxic-T-lymphocyte (CTL) epitope by Gambotto et al (2000) further defined EGFP as a model tumour antigen. Other workers have found that implantation of EGFP-expressing tumours in mice has induced the presence of anti-EGFP IgG antibodies in the serum (Brown et al, 2001;Spiotto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of EGFP 200 -208 as an H-2Kd-restricted cytotoxic-T-lymphocyte (CTL) epitope by Gambotto et al (2000) further defined EGFP as a model tumour antigen. Other workers have found that implantation of EGFP-expressing tumours in mice has induced the presence of anti-EGFP IgG antibodies in the serum (Brown et al, 2001;Spiotto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These mutant self-Ags can contribute to tumorigenesis, but different mutations are typically found in different examples of a particular type of tumor (50). In contrast, many of the alterations that are shared among tumors and are likely to drive different components of carcinogenesis represent normal, nonmutated self-Ags (51)(52)(53)(54)(55).…”
Section: Classes Of Tumor Agsmentioning
confidence: 99%
“…Recent studies have defined specific antibody responses to tumour-related antigens in patients with cancer 4 5 6 7 8. Since these antibodies are often triggered by changes in the structure or expression of self proteins in tumour cells,9 10 they may serve as potential immunological markers of cancer 11 12…”
mentioning
confidence: 99%